Early predictors of epilepsy and subsequent relapse in children with acute disseminated encephalomyelitis. (March 2020) - Rossor, Thomas; Benetou, Christina; Wright, Sukhvir; Duignan, Sophie; Lascelles, Karine; Robinson, Robert; Das, Krishna; Ciccarelli, Olga; Wassmer, Evangeline; Hemingway, Cheryl; Lim, Ming; Hacohen, Yael
Objective: To identify predictors of epilepsy and clinical relapses in children presenting with acute disseminated encephalomyelitis (ADEM). Methods: Children presenting with ADEM between 2005 and 2017 and tested clinically for MOG-Ab were identified from three tertiary paediatric neurology centres in the United Kingdom. Patients were followed up for a median of 6 years (range, 1–16 years). Results: A total of 74 children were studied (38 females; median age at first presentation: 4.5 years (range, 1.4–16 years)). MOG-Ab was positive in 50/74 (67.6%) of cases, and 27 (54%) of MOG-Ab positive children presented with a neurological relapse over time. MOG-Ab was more frequently positive in the relapsing group than in the monophasic group (27/31 vs 23/43; odds ratio 5.9 (95% CI: 1.8–19.7); p = 0.002). 16/74 (22%) children had seizures during the acute presentation with ADEM and 12/74 (16.2%) patients were diagnosed with post-ADEM epilepsy. The diagnosis of post-ADEM epilepsy was more frequently observed in children with relapsing disease than monophasic disease (10/31 vs 2/43; odds ratio 9.8 (95% confidence interval (CI): 2.0–48.7); p = 0.003), in children who had positive intrathecal oligoclonal bands than those with negative bands (4/7 vs 4/30; odds ratio 8.7 (95% CI: 1.4–54.0); p = 0.027) and in children who had positive MOG-Ab than negative MOG-Ab cases (11/12 vs 39/62; odds ratio 6.5 (95% CI:0.8–53.6); p = 0.051). Conclusion: A higher relapse rate and a greater risk of post-ADEM epilepsy in children with MOG-Ab-associated disease may indicate a chronic disease with immune-mediated seizures in these children.